2022
DOI: 10.3390/min12111363
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Enrichment Genesis of the Platinum Group Elements (PGEs) in Organic Rich Shale of the Wufeng and Longmaxi Formations of Upper Ordovician and Lower Silurian in the Sichuan Basin

Abstract: The petrology, mineralogy, elemental geochemistry, biology and PGEs characteristics of the black shale of the Wufeng and Longmaxi Formation in the CN outcrop of the Sichuan Basin are studied in this paper. The distribution and change in PGEs at different horizons are summarized, and the reasons for PGEs enrichment are discussed. The results show that the PGEs in the organic-rich shale segment are obviously enriched, which is positively correlated with the Total Organic Carbon (TOC) content and has a Pt–Pd dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…These events had a significant impact on the co-evolution of global geological environments and biota, leading to the widespread distribution of Lower Cambrian black shales. Previous research has indicated that the formation of black shale is facilitated by rapid marine transgressions, oceanic salinity stratification, stagnant water conditions, high biological productivity, extensive organic matter decomposition, and seafloor hydrothermal activity [22,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. However, the coupling relationship between the genesis of black shales and their depositional environment remains a subject of ongoing debate.…”
Section: Introductionmentioning
confidence: 99%
“…These events had a significant impact on the co-evolution of global geological environments and biota, leading to the widespread distribution of Lower Cambrian black shales. Previous research has indicated that the formation of black shale is facilitated by rapid marine transgressions, oceanic salinity stratification, stagnant water conditions, high biological productivity, extensive organic matter decomposition, and seafloor hydrothermal activity [22,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. However, the coupling relationship between the genesis of black shales and their depositional environment remains a subject of ongoing debate.…”
Section: Introductionmentioning
confidence: 99%